Pemanfaatan Limbah Kertas Sebagai Alat Cap Batik Guna Mendukung Inovasi Pada UMKM Batik Di Kelurahan Bendogerit - Amanda Okky Wijaya; Aulia Dwi Anggraeni; Ashaby Alamsyah; Nuruni Ika K. W (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
In general, the tools used to make batik stamps are mainly made of copper, which is quite expensive. So that it is only affordable by a few circles which causes batik stamps to be used by certain circles. As time goes by, innovations emerge in batik stamping tools made from waste paper which are cheap and easy to find. That way there are advantages and disadvantages of this batik stamp because of the nature of the paper which will be explained in this study. The method used in this study is the method of demonstration and practice or direct practice. The results showed that making paper-based batik stamps was quite simple, did not require a special process and could be done by yourself.